Assessment of thunderstorm neutron radiation environment at altitudes of aviation flights. Issue 2 (12th February 2013) - Drozdov, A.; Grigoriev, A.; Malyshkin, Y.
Abstract: [1] High‐energy radiation emitted from thunderclouds supposes generation of neutrons in photonuclear reactions of the gamma photons with air. This observation is supported by registration of neutrons during thunderstorm activity in a number of experiments, most of which established correlation with lightning. In this work we perform a modeling of the neutron generation and propagation processes at low atmospheric altitudes using current knowledge of the TGF source properties. On this basis we obtain dosimetric maps of thunderstorm neutron radiation and investigate possible radiation threat for aircraft flights. We estimate the maximal effective neutron dose that potentially can be received on board an aircraft in close proximity to the gamma source, to be of the order of 0.54 mSv over a time less than 0.1 s. This dose is considerably less than estimations obtained earlier for the associated electron and gamma radiation; nevertheless, this value is quite large by itself and under some circumstances the neutron component seems to be the most important for the dosimetric effect. Due to wide distribution in space, the thunderstorm neutrons are thought to also provide a convenient means for experimental investigation of gamma emissions from thunderclouds. To register neutrons from powerful gamma flashes that occur at the tops of thunderclouds, however, in the most favorable case one has to take a location above the 2 km level that is appropriate to mountains or aircraft facilities. Key Points: A large amount of neutrons can be generated owing to thunderstorm activity The neutron radiation can pose substantial hazard for airflights The neutron flashes can be used for investigation of TGFs and underlying physics